2020
DOI: 10.1111/echo.14603
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic parameters, speckle tracking, and brain natriuretic peptide levels as indicators of progression of indeterminate stage to Chagas cardiomyopathy

Abstract: Background Chronic Chagas cardiomyopathy (CCM) is characterized by a unique type of cardiac involvement. Few studies have characterized echocardiographic (Echo) transitions from the indeterminate Chagas disease (ChD) form to CCM. The objective of this study was to identify the best cutoffs in multiple Echo parameters, speckle tracking, and N‐terminal pro B‐type natriuretic peptide (NT‐proBNP) to distinguish patients without CCM (stage A) vs patients with myocardial involvement (stages B, C, or D). Methods Cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 51 publications
0
14
0
3
Order By: Relevance
“…It is important to emphasize that the results of our study, reinforcing previous data which showed that LV global myocardium deformation strain indexes GLS and GCS are still preserved in presumably early phases of CD [22,24,25], are indirectly corroborated by a more recent cross-sectional study in patients with different Chagas cardiomyopathy stages by Echeverría et al They also reported that a GLS value with a cut-off of -20.5% could detect the onset of myocardial alterations, despite the fact that this is not a low value of normality in most dedicated software [35].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 56%
“…It is important to emphasize that the results of our study, reinforcing previous data which showed that LV global myocardium deformation strain indexes GLS and GCS are still preserved in presumably early phases of CD [22,24,25], are indirectly corroborated by a more recent cross-sectional study in patients with different Chagas cardiomyopathy stages by Echeverría et al They also reported that a GLS value with a cut-off of -20.5% could detect the onset of myocardial alterations, despite the fact that this is not a low value of normality in most dedicated software [35].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 56%
“…In the absence of initial cardiac manifestations in infected patients, a yearly follow‐up of cardiac symptoms and electrocardiogram (ECG) seems essential: abnormalities should prompt cardiac work‐up, including echocardiography and ECG monitoring. If available, echocardiography to detect LV abnormalities is preferable, since the ECG is normal in about ∼10% of patients with LV abnormalities 112 …”
Section: Toxic Factorsmentioning
confidence: 99%
“…Multiple studies have found that patients in the indeterminate form may show incipient cardiac damage documented by abnormal longitudinal and radial strain of the LV compared to healthy controls [16,31]. Moreover, radial, circumferential, and longitudinal LV speckle-tracking strain values have been correlated with disease progression and the degree of myocardial fibrosis as measured by cardiac magnetic resonance imaging, highlighting the utility of this diagnostic method in CD and CCM [30,32]. In addition, speckle tracking strain has been shown to have clinical relevance in the prognostic assessment of patients with heart failure independently of LVEF.…”
Section: Discussionmentioning
confidence: 99%
“…At first, speckle tracking strain has the capacity of identifying subclinical myocardial dysfunction even in individuals with CD without symptoms, ECG, or conventional echocardiographic abnormalities (the so-called indeterminate form of the disease) [30]. Multiple studies have found that patients in the indeterminate form may show incipient cardiac damage documented by abnormal longitudinal and radial strain of the LV compared to healthy controls [16,31].…”
Section: Discussionmentioning
confidence: 99%